2017
DOI: 10.3892/ol.2017.6267
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes and pathways associated with bladder cancer based on co-expression network analysis

Abstract: Abstract. The aim of the present study was to identify hub genes and signaling pathways associated with bladder cancer (BC) utilizing centrality analysis and pathway enrichment analysis. The differentially expressed genes (DEGs) were screened from the ArrayExpress database between normal subjects and BC patients. Co-expression networks of BC were constructed using differentially co-expressed genes and links, and hub genes were investigated by degree centrality analysis of co-expression networks in BC. The enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
12
1
Order By: Relevance
“…For example, the expression of TMEM185A (transmembrane protein 185A) was tended to be down-regulated clones among patients with stage III serous ovarian carcinoma 19. TMPRSS11E (transmembrane protease, serine 11E) could suppress esophageal squamous cell carcinoma development by sensitizing cells to apoptosis under an apoptotic stimulus through downregulating the EGFR/AKT signaling pathway 20, but recently was found significantly upregulated in urinary bladder cancer patients 21, which was consistent with our study outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the expression of TMEM185A (transmembrane protein 185A) was tended to be down-regulated clones among patients with stage III serous ovarian carcinoma 19. TMPRSS11E (transmembrane protease, serine 11E) could suppress esophageal squamous cell carcinoma development by sensitizing cells to apoptosis under an apoptotic stimulus through downregulating the EGFR/AKT signaling pathway 20, but recently was found significantly upregulated in urinary bladder cancer patients 21, which was consistent with our study outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Genes showing increased expression in this region include three different transmembrane protease serine 11 genes (TMPRSS11d, e and g). TMPRSS11e is associated with decreased survival in iUC patients [67,68] and has been identified as a primary hub gene in coexpression networks marking iUC tumor progression [69]. This family of transmembrane proteins has not been extensively studied in iUC and, based on these results, is worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies only identified differentially expressed genes (DEGs) based on one database and there was a lack of validation when using other databases (Jia et al, 2015). Although some studies had validated their results through reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting, researchers only identified hub genes by constructing a co-expression network (Zhang et al, 2017) or a protein–protein interaction (PPI) network (Bi et al, 2015). In this study, we not only constructed a PPI network of DEGs to pick out hub genes, but also innovatively constructed a random forest model to further narrow down the number of hub genes in the PPI network by using these genes as features and their expression levels as feature values.…”
Section: Introductionmentioning
confidence: 99%